New trends in energy transition policies: citizens' involvement in the European energy market - Martinelli, Valerio (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the policies and regulations for the city energy governance section focuses on the challenges that urban energy planning commonly faces, providing food for thought to readers and fellow researchers. This contribution aims at examining these challenges and the solutions proposed in the scientific literature. For the first issue of TeMA Journal volume no. 17, this section is dedicated to the definition of policies and regulations for achieving the energy transition objectives at the European level.